Advances in Complement Research: from Pathophysiology to Precision Medicine - Joshua M. Thurman (Physiology, 2026)
The complement cascade is an evolutionarily ancient system of soluble and cell-bound proteins. Activation of the system triggers sequential proteolytic steps that rapidly generate downstream protein fragments, several of which have biologic activity. The complement system can directly lyse invasive pathogens, and it engages other cellular and molecular components of the immune system. In some contexts, complement also has counterregulatory immune effects and can dampen inflammation. Beyond its role in immunity, the complement cascade facilitates the clearance of injured cells and debris and can initiate tissue repair programs. Recent research has also shown that cleavage of complement proteins within cells mediates homeostatic functions and signaling pathways. Although the complement system plays an essential role in protecting the host from infection, inappropriate or uncontrolled complement activation mediates tissue inflammation across a large spectrum of autoimmune, inflammatory, and degenerative diseases. Complement-inhibitory drugs have been developed to prevent these maladaptive effects, and several of these drugs have been approved for clinical use. These drugs block an arm of the immune system that is not directly affected by other immunosuppressive agents. Given the diverse functions of complement, its role in disease, and the development of anticomplement drugs, complement biology will remain an important topic of research in the foreseeable future.